The effect of quality control standard implementation for quality improvement of the casting process on the jewellery manufacturing industry - Erwin; Chan, Yefri; Lenardo, Yovi; Supriatna, Ade; Faturachman, Danny (2477 - 6165, 2024)
The high demand for jewellery products increases significantly every year, but the export requirements of the products demand high quality. So, efforts are needed to improve quality, support cost savings, reduce energy needs, and improve work safety, especially in the casting process of jewellery products. This study aims to analyze the implementation of practical quality control standards to improve the quality of jewellery product casting. This research method uses a Plan-Do-Check-Action process approach that refers to ISO 9001, 14001 and 45001 standards. Implementing the PDCA (Plan-Do-Check-Action) process approach adopted in developing quality control methods in the jewellery casting process proved effective, resulting in casting shrinkage of 0.2 kg below the established standard of 0.7 – 1 kg. Controlling temperature casting below the melting point can also provide energy savings and heat control of the casting process to reduce occupational safety and health hazards. PDCA quality control methods can improve the quality of casting jewellery products by reducing porosity defects and shrinkage, saving energy, and reducing occupational safety hazards. This research provides an effective quality control method for the jewellery casting production process regarding quality improvement, environmental management, and safety to achieve the Company's sustainability.